If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 156 = -6(-7n + -5) Reorder the terms: 156 = -6(-5 + -7n) 156 = (-5 * -6 + -7n * -6) 156 = (30 + 42n) Solving 156 = 30 + 42n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-42n' to each side of the equation. 156 + -42n = 30 + 42n + -42n Combine like terms: 42n + -42n = 0 156 + -42n = 30 + 0 156 + -42n = 30 Add '-156' to each side of the equation. 156 + -156 + -42n = 30 + -156 Combine like terms: 156 + -156 = 0 0 + -42n = 30 + -156 -42n = 30 + -156 Combine like terms: 30 + -156 = -126 -42n = -126 Divide each side by '-42'. n = 3 Simplifying n = 3
| 6-6x=5x-15+18 | | -3=-3(2-1) | | 5(2x-12)+3=-1 | | -152=19r | | 9x-17=5x+7 | | -20=-2+8m+6 | | 2x+3(x-2)=-2+8x+8 | | 4x-2[x-3]=2+4x+4 | | 7r+5s=36 | | 6x+4=6x-2 | | 0+7(25)=175 | | 3[x-6]+2=5x-2 | | 2(x^2-49)-12=8 | | 5+6=47 | | b+7(25)=175 | | 3x=(x+2+x+4)-1 | | -7.5=-9.9-m | | 24=6m-4-2m | | 6x+6=-9 | | 4x^2-16x-56=0 | | 1-8x-2=23 | | 2x+35=10-37 | | 2y+2-4x=0 | | 2(5x+3)-(7x+1)=-88 | | -35-2.5x=-95 | | -6(6+2w)=-8w-2w | | 3x+2y-6=4y+4 | | Y=3(.55)x | | w=a+4+3 | | w=(a+4)+3 | | Q(Q+3)=5Q+3 | | 13=5n+8n |